Do Generic Proofs Improve Proof Comprehension? - Kristen Lew; Keith Weber; Juan Pablo Mejía Ramos (Korea Society of Educational Studies in Mathematics, 2020)
Students often have difficulty understanding the proofs that they read. Some mathematics educators have suggested using generic proofs to improve students' proof comprehension. However, few empirical studies about students' perceptions of generic proofs or whether students understand generic proofs better than traditional proofs have been conducted. In this paper, we describe a qualitative interview study and a quantitative experimental study exploring these issues. Our first finding is that generic proofs are popular with students, who believe they have the potential to improve proof comprehension. Our second finding is that in a randomized controlled experiment, students did not learn more from reading a generic proof than a traditional proof. The significance of these findings is discussed at the end of the paper.